2013
DOI: 10.1016/j.bbamem.2012.09.018
|View full text |Cite
|
Sign up to set email alerts
|

Alternative splicing: Functional diversity among voltage-gated calcium channels and behavioral consequences

Abstract: Neuronal voltage-gated calcium channels generate rapid, transient intracellular calcium signals in response to membrane depolarization. Neuronal CaV channels regulate a range of cellular functions and are implicated in a variety of neurological and psychiatric diseases including epilepsy, Parkinson’s disease, chronic pain, schizophrenia, and bipolar disorder. Each mammalian Cacna1 gene has the potential to generate tens to thousands of CaV channels by alternative pre-mRNA splicing, a process that adds fine gra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
98
0

Year Published

2013
2013
2019
2019

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 108 publications
(99 citation statements)
references
References 127 publications
(139 reference statements)
1
98
0
Order By: Relevance
“…Ten different genes encode the Ca v ␣ 1 subunits, whereas the ␤ and ␣ 2 ␦ subunits are encoded by four genes each (5,6). Alternative splicing further adds to the molecular and functional diversity of ␣ 1 and ␤ subunits (1,7).…”
Section: Camentioning
confidence: 99%
“…Ten different genes encode the Ca v ␣ 1 subunits, whereas the ␤ and ␣ 2 ␦ subunits are encoded by four genes each (5,6). Alternative splicing further adds to the molecular and functional diversity of ␣ 1 and ␤ subunits (1,7).…”
Section: Camentioning
confidence: 99%
“…The variety of calcium channel types required to support such diversity of function is achieved by both extensive alternative splicing of subunit genes and the various combinations with which the subunits coassemble (Bourinet et al 1999;Krovetz et al 2000;Lipscombe 2005;Lipscombe and Raingo 2007;Lipscombe et al 2013), the result being the generation of multiple channels with each showing finely tuned biophysical properties tailored to cell-and network-specific roles. Here, we focus on two functions that, in particular, have implications for seizure gen-eration, their presynaptic involvement in neurotransmitter release, and their role in burst firing.…”
Section: Physiological Roles Of Calcium Channels In Neuronsmentioning
confidence: 99%
“…Additional studies using Nova knockout mice have revealed functions for specific Nova-regulated splice variants (including alternative exons in the Dab1 gene) that facilitate the proper migration of newly born cortical neurons (Yano et al 2010) and exons in the Agrin gene that are important for the formation of NMJs (Ruggiu et al 2009). However, aside from these examples, few other neuronal genes have been characterized at isoform resolution in vivo (Norris and Calarco 2012;Lipscombe et al 2013b;Zheng and Black 2013).…”
mentioning
confidence: 99%